 21.18. ON PSEUDOFUNCOIDS

365

Obvious

1845

.

Pseudofuncoid is just a staroid of the form (

F

(

A

)

,

F

(

B

)).

Obvious

1846

.

[

f

] is a pseudofuncoid for every funcoid

f

.

Example

1847

.

If

A

and

B

are infinite sets, then there exist two different

pseudofuncoids

f

and

g

from

A

to

B

such that

f

(

T

A

×

T

B

) =

g

(

T

A

×

T

B

) =

[

c

]

(

T

A

×

T

B

) for some funcoid

c

.

Remark

1848

.

Considering a pseudofuncoid

f

as a staroid, we get

f

(

T

A

×

T

B

) =

f

.

Proof.

Take

f

=

(

X

,

Y

)

X ∈

F

(

A

)

,

Y ∈

F

(

B

)

,

T

X

and

T

Y

are infinite

and

g

=

f

(

X

,

Y

)

X ∈

F

(

A

)

,

Y ∈

F

(

B

)

,

X w

a,

Y w

b

where

a

and

b

are nontrivial ultrafilters on

A

and

B

correspondingly,

c

is the funcoid

defined by the relation

[

c

]

=

δ

=

(

X, Y

)

X

P

A, Y

P

B, X

and

Y

are infinite

.

First prove that

f

is a pseudofuncoid. The formulas

¬

(

I

f

) and

¬

(

f

I

) are

obvious. We have

I t J

f

K ⇔

\

(

I t J

) and

\

Y

are infinite

\

I ∪

\

J

and

\

Y

are infinite

\

I

or

\

J

is infinite

\

Y

is infinite

\

I

and

\

Y

are infinite

\

J

and

\

Y

are infinite

I

f

K ∨ J

f

K

.

Similarly

K

f

I t J ⇔ K

f

I ∨ K

f

J

. So

f

is a pseudofuncoid.

Let now prove that

g

is a pseudofuncoid. The formulas

¬

(

I

g

) and

¬

(

g

I

)

are obvious. Let

I t J

g

K

. Then either

I t J

f

K

and then

I t J

g

K

or

I t J w

a

and then

I w

a

∨ J w

a

thus having

I

g

K ∨ J

g

K

. So

I t J

g

K ⇒ I

g

K ∨ J

g

K

.

The reverse implication is obvious. We have

I t J

g

K ⇔ I

g

K ∨ J

g

K

and

similarly

K

g

I t J ⇔ K

g

I ∨ K

g

J

. So

g

is a pseudofuncoid.

Obviously

f

6

=

g

(

a g b

but not

a f b

).

It remains to prove

f

(

T

A

×

T

B

) =

g

(

T

A

×

T

B

) = [

c

]

(

T

A

×

T

B

).

Really,

f

(

T

A

×

T

B

) = [

c

]

(

T

A

×

T

B

) is obvious. If (

A

X,

B

Y

)

g

(

T

A

×

T

B

) then either (

A

X,

B

Y

)

f

(

T

A

×

T

B

) or

X

up

a

,

Y

up

b

, so

X

and

Y

are infinite and thus (

A

X,

B

Y

)

f

(

T

A

×

T

B

). So

g

(

T

A

×

T

B

) =

f

(

T

A

×

T

B

).

Remark

1849

.

The above counter-example shows that pseudofuncoids (and

more generally, any staroids on filters) are “second class” objects, they are not

full-fledged because they don’t bijectively correspond to funcoids and the elegant

funcoids theory does not apply to them.

From the above it follows that staroids on filters do not correspond (by restric-

tion) to staroids on principal filters (or staroids on sets).